The hyperinflation crisis in the urban residential properties market of Zimbabwe (2000 .2005): some stakeholders’ views - Matongo, Alois Rewai (Midlands State University, 2015)
This paper presents results of a research, carried out in the urban residential accommodation sector, between August 2004 and February 2005.The research, carried out in Zimbabwe s foremost metropolitan cities of Harare, Bulawayo, Mutare and Gweru, sought to establish perceptions of key stakeholder organizations in the sector on the nature and dynamics of the factors behind the residential properties hyperinflation crisis bedeviling the sector and the most lasting solution to the problem. Factors perceived by stakeholder organizations to be most responsible for this crisis of wildly rising prices and rentals of urban residential houses are speculative activities of Zimbabweans living and working abroad and profiteering tendencies of some real estate agents and high net worth individuals. Price and rent control, controlled auction market and strict implementation of the one-person-one-house policy, among others, were perceived as the most lasting solutions to the crisis.